Power politics - Roy, Arundhati 1961- (South End Press, 2001)
The acclaimed novelist criticizes globalization, particularly as it manifests in Indian dam construction, and challenges the idea that only "experts" can criticize social and economic policy.
Keywords: Politik; Protest; Staudamm; Energiepolitik; Inde - Politique et gouvernement - 1977-; Indien; India -- Politics and government -- 1977-; Narmada; Aufsatzsammlung